INTEGRATION OF INFORMATION TECHNOLOGY AND DEVELOPMENT OF STUDENTS’ CRITICAL THINKING - Sayidova Mekhrinoz O‘ktamjon qizi (Web of Journals Publishing, 2025)
This article analyzes the role of information technology in developing students’ critical thinking skills. As digital technologies become increasingly important in modern education, it is essential for students to acquire the ability to think independently, analyze problems, and develop alternative solutions. The article explores the impact of information technologies on the learning process, their influence on students’ cognitive development, and their contribution to enhancing critical thinking. Additionally, modern approaches and methods related to this topic are discussed.
Keywords: Information technologies, critical thinking, digital education, interactive teaching, problem thinking, innovative methods, educational process, modern pedagogy, data analysis, creative thinking, digital literacy, analytical thinking, artificial intelligence, online educational platforms, digital resources.